Розробка імітаційної моделі вантажного вагона з метою отримання оцінки динамічних показників - Шовкун, Вадим Олександрович (НТУ "ХПІ", 2017)
Розглянуто результати моделювання динамічного процесу навантаження буксового вузла використовуючи комплекс "UM Универсальный механизм". Розроблена в "UM" імітаційна модель "вагон-залізнична колія" включає в себе кузов напіввагону з можливістю імітувати різну ступінь завантаженості. Отримані реалізації для коефіцієнтів вертикальної та горизонтальної динаміки в діапазоні швидкостей руху від 4+0 до 120 км/год як на прямих, так і в кривих дільницях колії. Доведено, що результати моделювання підпорядковуються нормальному закону розподілення. Визначені основні параметри, що характеризують ці процеси в залежності від швидкості та режиму руху.

Considered to improve the reliability of axle equipment is complex and requires an integrated approach for their solution. It is therefore necessary to explore ways of improving existing and creating new designs axle unit. These challenges require an integrated approach which one of the steps is determining the probabilistic loads acting on the elements of the chassis of freight cars. To model the dynamic process of loading axle unit used a series of "UM Universal mechanism", developed in Bryansk state technical University. Developed in "UM" simulation model "car-railway track" includes a body napavine with the capability to simulate varying degrees of workload, trucks of model 18-100 with the ability to change their characteristics, and the model of the elastic way that allows you to change the profile and the macro-geometry of the path. The obtained simulation results obey normal distribution. The main parameters characterizing these processes depending on speed and driving mode. Further using the obtained data, calculated correlation functions of random processes that characterize the combined effect of change of coefficients of horizontal and vertical dynamics of wagon Built correlation functions allows to evaluate the reliability of the axle unit. Modeling of dynamic loads acting on the running parts of freight cars showed sufficient convergence with the results of sea trials of 87%.
Development of simulation model of freight car with the aim of obtaining estimates of dynamic parameters
Keywords: буксовий вузол; підшипник; піввагон; колісна пара; показники Калмагорова-Смирнова; axle box; bearing assemblies; pair of wheels